Multi-objective Geometric Programming with Varying Parameters: Application in Waste Water Treatment System - Jana, Mrinal; Panda, Geetanjali (Mathematical Modelling and Analysis, 2015)
In this paper a general multi-objective geometric programming problem with interval parameters is proposed, and a methodology is developed to derive its solution. The model is transformed into a general geometric programming problem, and relation between the original problem and the transformed problem is established. Application of this discussion is illustrated in a waste water treatment model.